2012
DOI: 10.1021/jp303425g
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of Conducting Polymers Using UV Lithography: The in-Situ Polymerization Approach

Abstract: We report on the in-situ polymerization of 3T with Cu(ClO4)2 inside several host polymers such as Novolak-based negative-tone photoresist, polystyrene (PS), poly(4-vinylphenol) (P4VP), poly(methyl methacrylate) (PMMA), and poly(4-vinylphenol)-co-(methyl methacrylate) (P4VP-co-MMA) to form an interpenetrating polymer network (IPN). Conducting IPN films in the order of 10–4–150 S/cm are obtained depending on the specific IPN composition. Moreover, the convenience of this synthetic approach has been demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
(81 reference statements)
0
17
0
Order By: Relevance
“…This method can also be used to modify the conductivity of numerous insulating polymers while preserving their physical and chemical properties 190. Abargues et al have reported photolithography process for polymerization of terthiophene (3T) with Cu(ClO 4 ) 2 inside several host polymers such as Novolak‐based negative‐tone photoresist, PS, poly(4‐vinylphenol) (P4VP), PMMA, and poly(4‐vinylphenol)‐ co ‐(methyl methacrylate) (P4VP‐ co ‐MMA) for developing interpenetrating polymer network (IPN) ( Figure a) . A spin‐coated UV‐patternable polymer containing 3T and Cu(ClO 4 ) 2 was exposed to UV light, baked, and developed.…”
Section: Surface Modification Through Patterningmentioning
confidence: 99%
See 1 more Smart Citation
“…This method can also be used to modify the conductivity of numerous insulating polymers while preserving their physical and chemical properties 190. Abargues et al have reported photolithography process for polymerization of terthiophene (3T) with Cu(ClO 4 ) 2 inside several host polymers such as Novolak‐based negative‐tone photoresist, PS, poly(4‐vinylphenol) (P4VP), PMMA, and poly(4‐vinylphenol)‐ co ‐(methyl methacrylate) (P4VP‐ co ‐MMA) for developing interpenetrating polymer network (IPN) ( Figure a) . A spin‐coated UV‐patternable polymer containing 3T and Cu(ClO 4 ) 2 was exposed to UV light, baked, and developed.…”
Section: Surface Modification Through Patterningmentioning
confidence: 99%
“…a) Scheme of the fabrication of the conducting interpenetrating polymer network (IPN) patterns. Reproduced with permission . Copyright 2012, American Chemical Society.…”
Section: Surface Modification Through Patterningmentioning
confidence: 99%
“…Generally, photoresist is an electronic insulator in its pure (i.e., undoped) state. In order to significantly increase the conductivity of the polymerized material, other composites, such as terthiophene (3T) with copper (II) perchlorate, carbon black particles, silver or protonically doped polyaniline nanoparticles have to be added. However, these Electrically Conductive Polymer Composites (ECPCs) have several restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…The examples of conductive fillers are terthiophene (3T) with copper (II) perchlorate [7], silver nanoparticles [8], graphite [9] or carbon black particles [10], protonically doped polyaniline (PANI) nanoparticles [11], and others [12,13]. However, these materials have several limitations: (1) the addition of filler particles requires control of material viscosity by addition of various solvents, influencing the photo-polymerization process;…”
Section: Introductionmentioning
confidence: 99%
“…(3) the resolution is constrained to 10 -30 μm because of the light diffraction by filler particles [7,8,9]; (4) and finally, the cured material has low optical transparency over the visible range.…”
Section: Introductionmentioning
confidence: 99%